Structure and properties of dislocations and the twin boundary on (101) in β-cyclotetramethylene tetranitramine. Issue 11 (3rd June 2022) - Cawkwell, M. J.; Mohan, N.; Zecevic, Milovan; Luscher, D. J.; Ramos, K. J.
ABSTRACT: Dispersion-corrected density functional theory calculations of the generalised stacking fault energy surface of the (101) plane in monoclinic β -cyclotetramethylene tetranitramine ( β -HMX) indicate that a stacking fault with an energy of approximately 130 mJ/m 2 at the translation vector t = 1 / 2 [ 11 1 ¯ ] is metastable. Using the energy of the metastable stacking fault and anisotropic linear elasticity theory, we have evaluated whether dislocations with total Burgers vectors b = [ 010 ], [ 10 1 ¯ ] and [ 11 1 ¯ ] will split into partial dislocations on ( 101 ) . Our results suggest that it is not favourable for the [ 010 ] screw dislocation to split into 1 / 2 〈 11 1 ¯ 〉 partials but that the edge dislocation will split into partials separated by a narrow, 19.8 Å, stacking fault. Both screw and edge [ 11 1 ¯ ] dislocations are predicted to split into two partials with splitting distances of about 28.7 and 43.4 Å, respectively. The screw and edge [ 10 1 ¯ ] dislocation are also predicted to split into partials, with equilibrium distances of 16.3 and 43.2 Å, respectively. These results are consistent with recent analyses of Knoop indentation experiments in which the ( 101 ) [ 010 ] slip system is inactive whereas [ 10 1 ¯ ] dislocations are glissile. Since twinning is an important deformation mechanism in β -HMX, dispersion-corrected density functional theory calculations have also been used to compute the energy of the ( 101 ) [ 10 1 ¯ ] twin boundary, for which we report a value of 163 mJ/m 2 .